Estudo e desenvolvimento de conversores cc-cc com elevado ganho de tensão baseados na topologia do SEPIC isolado - Andres, Bernardo (2022)
This Doctoral Thesis makes a detailed study and development of topologies of dc-dc converters with high voltage gain for photovoltaic microinverters. This requirement is because of low voltage of photovoltaic module, which has to be suitable for the high voltage of inverter dc bus. Due to low power of this system, the isolated SEPIC is chosen as standard topology for synthesis of others converters, because it uses a single semiconductor switch, besides providing galvanic isolation among photovoltaic module and electrical grid. To solve some problems of this converter, besides providing a higher static gain, some cells are added to converter and analyzed. The topologies obtained and defined as most promising and more relevant are selected to be analyzed with more detailing. The proposed converters are deeply analyzed as to its operation and equation for operation analysis and definition of voltage and current stress. All the analyzed converters show a characteristic of resonant operation, which brings the advantage of soft switching, reducing the switching losses. Besides that, they are capable to solve some problems of isolated SEPIC, such as the replacement of coupled inductor by the transformer, besides mitigating voltage spikes on secondary side, and decreasing voltage stress over some components. Lastly, and not less important, the static gain is significatively increased, without the excessive addition of components. To validate all the concepts, assumptions and equations performed, experimental results are presented. These results aim to verify the compatibility among converters waveforms, besides issues of soft switching, listing some advantages and disadvantages of each converter, also presenting the efficiency curves and the loss estimation for each converter. In this way, this work aims to contribute making a detailed study and developing converters to be used on a photovoltaic microinverter. To affirm this propose, experimental results are obtained and presented, in order to make a theoreticalexperimental comparison among topologies of converters, aiming to improve the quality and trustworthiness of this work.